A Directed Reading-Thinking Activity (Dr-Ta) Towards Students ‘Critical Reading - Sudirman Sudirman; Edi Firman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
This current study aimed to find out whether DR-TA (Directed Reading- Thinking Activity) had a significant effect on the critical reading skills of the English department students of FPBS IKIP Mataram  or  not.The population of this research was 238  students and the samples were taken by using cluster random sampling technique the sample was 80 students which was consisted of 41 students in the control group and 39 students in the experimental. This research is quantitative with a quasi-experimental design: the non-equivalent control group design. To obtain the data needed, the instrument was administered namely tests  which was consisted of pre-test and post-test. Pre-test was applied to obtaining the primary data meanwhile the post-test was applied after the treatment accomplished. The data on the reading test was analyzed by using descriptive statistic and inferential statistics. The result of data analysis showed that the experimental group mean score on pre-test was 62.5 and posttest was 73.07, meanwhile the result of  control group means score on pre-test was 57.92 and post-test 64.25. There was an improvement of the students in each group from pre-test to post test. And the result hypothesis or inferential analysis proved that t-test score was higher than the result t-table (3.843>1.990) with degree of freedom (df) was 75 in significant level 95% or α = 0.05. It can be concluded that DR-TA Strategy has significant effect on critical reading skills of the English department students of FPBS IKIP Mataram. The effect was significant because DR-TA Strategy lead the students to have prediction before reading, create background knowledge, analyzing the fact to support the prediction, confirming the prediction and evaluating the text and context in order to have comprehensive comprehension. The results of this research hopefully could be an alternative strategy in teaching critical thinking in reading and could be reference for further researchers